2015
DOI: 10.1158/0008-5472.can-14-1623
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced MET Translation and Signaling Sustains K-Ras–Driven Proliferation under Anchorage-Independent Growth Conditions

Abstract: Oncogenic K-Ras mutation occurs frequently in several types of cancers including pancreatic and lung cancers. Tumors with K-Ras mutation are resistant to chemotherapeutic drugs as well as molecular targeting agents. Although numerous approaches are ongoing to find effective ways to treat these tumors, there are still no effective therapies for K-Ras mutant cancer patients. Here we report that K-Ras mutant cancers are more dependent on K-Ras in anchorage independent culture conditions than in monolayer culture … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 38 publications
(36 reference statements)
5
48
1
Order By: Relevance
“…4B , left). Despite the lack of growth inhibition in some lines, we found that ARS-853 effectively inhibited RAF-RBD KRAS dependence is well established to be more pronounced in 3-D and/or anchorage-independent settings than in adherent growth assays (10)(11)(12). In line with gene-targeted approaches (10)(11)(12), all tested KRAS G12C cell lines were robustly inhibited by ARS-853 in soft-agar colony formation assays with an average ∼ 2 μ mol/L IC 50 ( Fig.…”
Section: G12smentioning
confidence: 73%
“…4B , left). Despite the lack of growth inhibition in some lines, we found that ARS-853 effectively inhibited RAF-RBD KRAS dependence is well established to be more pronounced in 3-D and/or anchorage-independent settings than in adherent growth assays (10)(11)(12). In line with gene-targeted approaches (10)(11)(12), all tested KRAS G12C cell lines were robustly inhibited by ARS-853 in soft-agar colony formation assays with an average ∼ 2 μ mol/L IC 50 ( Fig.…”
Section: G12smentioning
confidence: 73%
“…In an esophagogastric cancer patient treated with a MET inhibitor, a KRAS mutation was discovered as a novel cause of acquired resistance (50). Whereas in KRAS-addicted cancer cells, KRAS mediated MET expression via increased MET translation and promoted “KRas addiction” in anchorage-independent conditions (51). Given the pleiotropic effects of MET activation (10) and its emerging role in therapy resistance (52,53), these data provide strong rationale for further exploration of MET-RAS and RAS-MET signal interactions in NF1-related MPNSTs.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation is a key initiator, as evidenced by its presence in PanIN lesions (Kanda et al 2012;Murphy et al 2013) and the production of PanIN lesions in oncogenic Kras-driven GEMMs (Hezel et al 2006;Perez-Mancera et al 2012a). While some PDAC cell lines in two-dimensional (2D) culture can tolerate shRNA-mediated KRAS extinction (Singh et al 2009), most PDAC cells remain highly addicted to oncogenic KRAS for tumor maintenance in three-dimensional (3D) culture (Zhang et al 2006;Fujita-Sato et al 2015) and inducible oncogenic Kras GEMMs with advanced tumors (Collins et al 2012;Ying et al 2012). These data strongly support the view that KRAS is a prime therapeutic target for PDAC.…”
Section: The Kras Oncogene Signaling Networkmentioning
confidence: 99%